2016
DOI: 10.1097/dad.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Depth and Patterns of Adnexal Involvement in Primary Extramammary (Anogenital) Paget Disease: A Study of 178 Lesions From 146 Patients

Abstract: Extramammary Paget disease (EMPD) is a rare neoplasm usually presenting in the anogenital area, most commonly in the vulva. Adnexal involvement in primary EMPD is a very common feature and serves as a pathway for carcinoma to spread into deeper tissue. The depth of carcinomatous spread along the appendages and the patterns of adnexal involvement were studied in 178 lesions from 146 patients with primary EMPD. Hair follicles and eccrine ducts were the adnexa most commonly affected by carcinoma cells. The maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
2
11
1
7
Order By: Relevance
“…In contrast, we have previously shown that cutaneous adnexa including hair follicles, sebaceous glands, and apocrine and eccrine units may present a path for carcinomatous spread into deeper tissues in cases of EMPD, as they are involved in almost all cases. 7,22 A similar situation may be presumed with respect to AGMLG. We noticed several patterns of colonization of AGMLG by neoplastic cells.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In contrast, we have previously shown that cutaneous adnexa including hair follicles, sebaceous glands, and apocrine and eccrine units may present a path for carcinomatous spread into deeper tissues in cases of EMPD, as they are involved in almost all cases. 7,22 A similar situation may be presumed with respect to AGMLG. We noticed several patterns of colonization of AGMLG by neoplastic cells.…”
Section: Discussionmentioning
confidence: 74%
“…If our proposition is confirmed in subsequent studies, this may result in a reevaluation of current therapeutic approaches to primary EMPD, especially with respect to local surgical and nonsurgical treatment, which should take into consideration both the depth of secondary adnexal involvement (up to 3.6 mm) and the depth of location of AGMLG (up to 3.9 mm) as a possible source of disease, including recurrences, which have a rate that ranges currently from 12% to 57%. 3,22,32…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Опухоль развивается чаще у женщин белой расы, обычно в период менопаузы [2]. Возраст заболевших варьирует от 40 до 95 лет и в среднем составляет 71 год [14]. Хотя возраст пациентки, которую мы наблюдали, не достигал 70 лет, она находились в менопаузе.…”
Section: Discussionunclassified